Assessment of Adoption, Market Potential and Environmental Impact of Carbonized Briquettes Among Farmers in Western Uganda’s Beef-Producing Regions - Nakiganda, Annuciate; Wamubirigwe, Bernard; Mubiru, Sarah; Bugeza, James; Kigozi, Abasi; Mugerwa, Swidiq; Kigongo, John; Kayiwa, Stephen; Sserumaga, Pyton; Namwanje, Joan; Kivumbi, Achileo; Serwadda, Joseph; et al. (International Journal of Economy, Energy and Environment, 2023)
A lot of agricultural residues are generated each year in developing and developed countries. About 60-70% of the total Agricultural biomass is left in the fields annually in Uganda. Making Briquettes helps to turn waste into wealth, saves money and provides an alternative for firewood and charcoal. This study was developed to assess the adoption and market potential of carbonized briquette production among farmers in beef producing communities in Uganda. NARO introduced briquettes making in the beef producing communities of Isingiro, Mbarara and Masindi districts. After four months, an adoption study was conducted to determine how many farmers continued to produce, use and sell the briquettes. Approximately 58.2%, 50.6% and 66.7% farmers were found producing and using briquettes in Isingiro, Masindi and Mbarara districts respectively. Farmers mostly used cow dung (82%) as binders and charcoal dust (83%) as class B material. Over 93% farmers used briquettes to cook their food while 57.4% saved money on buying traditional fuels, and 49.5% mentioned that briquettes lasted longer while cooking respectively. Farmers in all the three districts produced 447.5 basins of briquettes which generated 6,712,500shs in revenue at a price of 15,000shs/basin of briquettes. Briquettes making can help the farmers in beef producing communities to earn income, while reducing agricultural waste, tree cutting and protecting the environment.